The Activity of 1,8-Dihydroanthraquinone Derivatives in Nervous System Cancers - Estera Okoń; Wirginia Kukula-Koch; Agata Jarząb; Katarzyna Gaweł-Bęben; Ewelina Bator; Magdalena Michalak-Tomczyk; Jacek Jachuła; Beata Antosiewicz-Klimczak; Adrian Odrzywolski; Wojciech Koch; Anna Wawruszak (Molecules)
Primary and metastatic tumors of the nervous system represent a diverse group of neoplasms, each characterized by distinct biological features, prognostic outcomes, and therapeutic approaches. Due to their molecular complexity and heterogeneity, nervous system cancers (NSCs) pose significant clinical challenges. For decades, plants and their natural products with established anticancer properties have played a pivotal role in the treatment of various medical conditions, including cancers. Anthraquinone derivatives, a class of tricyclic secondary metabolites, are found in several botanical families, such as Fabaceae, Polygonaceae, Rhamnaceae, and Rubiaceae. In a comprehensive review, recent advancements in the anticancer properties of 1,8-dihydroanthraquinone derivatives—such as emodin, aloe-emodin, hypericin, chrysophanol, rhein, and physcion—were analyzed. These compounds have been studied extensively, both used individually and in combination with other chemotherapeutic agents, using in vitro and in vivo models of nervous system tumors. It was demonstrated that 1,8-dihydroanthraquinone derivatives induce apoptosis and necrosis in cancerous cells, intercalate into DNA, disrupting transcription and replication in rapidly dividing cells, and alter ROS levels, leading to oxidative stress that damages tumor cells. Additionally, they can influence signaling pathways involved in oncogenesis, such as MAPK, PI3K/Akt, or others crucial for the survival and the proliferation of NSC cells. The exploration of 1,8-dihydroanthraquinone derivatives aims to develop novel therapies that could overcome resistance and improve cancer patients’ outcomes.